Determinants of inclusive development of municipal establishments (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. The article investigates the theoretical and applied aspects of inclusive development of territorial communities, outlines its main determinants and identifies ways to ensure. The methodological approach substantiates the need for inclusive development of local communities, which involves the creation of investment-attractive, gender-oriented, comfortable, environmentally friendly local communities with developed infrastructure, small and medium businesses, effective governance and an active community of people, where everyone a member of the community can realize their potential and meet their needs regardless of age, gender, physical abilities, nationality and religion.Goal. The goal of the article is to substantiate the need for inclusive development of municipalities, outlining its main determinants and ways to achieve it.Methods. The following methods were used for scientific research: method of structural analysis, method of system analysis, method of abstract-logical generalization.Results. The article studies the preconditions and investigates the chronology of the concept of inclusive design. Theoretical analysis of the concept of «universal design» and its relationship with the concepts of «inclusive design», «affordable design», «design for all», «barrier-free design», «design for users». It is established that all these concepts are interchangeable. The necessity of using the concept of inclusive design for the formation of the living environment of territorial communities, convenient and accessible to all residents regardless of age, gender, culture, etc. is substantiated. To ensure the inclusive development of local communities, it is proposed to use the following principles of universal design: the principle of equal use, the principle of flexibility in use, the principle of simple and convenient use, the principle of perception of information regardless of user sensory capabilities, the principle of error, low size and space in the approach, entrance and various manipulations, despite the anthropometric characteristics, condition and mobility of members of the local community. It is substantiated that the inclusive living environment of territorial communities allows all members of society to feel more comfortable, especially: parents with young children; children in schools; patients in hospitals; children under 7 years; the elderly; people with disabilities; pregnant women; people with a large body weight; people of short or tall stature; to any person, if in a certain period of time he is less attentive or less mobile, etc.Conclusions: the organization of living space of territorial communities on the basis of the principles of inclusive design will allow: to create conditions for equal access of citizens to fundamental rights and freedoms; improve the quality of life of the population and ensure equal access to the resources and benefits available to local communities, regardless of gender, age, mobility and physical capabilities.